2017
DOI: 10.1038/s41598-017-08596-5
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 mediated one-step disabling of pancreatogenesis in pigs

Abstract: Genome editing using programmable nucleases has revolutionized biomedical research. CRISPR-Cas9 mediated zygote genome editing enables high efficient production of knockout animals suitable for studying development and relevant human diseases. Here we report efficient disabling pancreatogenesis in pig embryos via zygotic co-delivery of Cas9 mRNA and dual sgRNAs targeting the PDX1 gene, which when combined with chimeric-competent human pluriopotent stem cells may serve as a suitable platform for the xeno-genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 15 publications
0
33
0
1
Order By: Relevance
“…(), who reported that supplementation with 50 μmol/L CGA is advantageous to the porcine IVP system. When porcine zygotes from oocytes matured with or without 50 μmol/L CGA were electroporated with Cas9 messenger RNA and single guide RNA targeting sites in pancreatic duodenal homeobox‐1 ( Pdx1 ) gene (Wu et al., ), the proportion (89.3%, 25/28) of blastocysts with a mutated sequence in the CGA‐treated group was similar with that (88.2%, 30/34) in the untreated group (data not shown). These observations indicate that CGA supplementation during maturation culture may increase the number of embryos with insertions or deletions (indels) in the targeted gene by electropolation.…”
Section: Discussionmentioning
confidence: 91%
“…(), who reported that supplementation with 50 μmol/L CGA is advantageous to the porcine IVP system. When porcine zygotes from oocytes matured with or without 50 μmol/L CGA were electroporated with Cas9 messenger RNA and single guide RNA targeting sites in pancreatic duodenal homeobox‐1 ( Pdx1 ) gene (Wu et al., ), the proportion (89.3%, 25/28) of blastocysts with a mutated sequence in the CGA‐treated group was similar with that (88.2%, 30/34) in the untreated group (data not shown). These observations indicate that CGA supplementation during maturation culture may increase the number of embryos with insertions or deletions (indels) in the targeted gene by electropolation.…”
Section: Discussionmentioning
confidence: 91%
“…Pancreatic duodenal homeobox 1 ( PDX1 , also known as IPF‐1 , IDX‐1 , and STF‐1 ) is a crucial gene for pancreas development during the fetal period (Bonal & Herrera, 2008; Jonsson, Carlsson, Edlund, & Edlund, 1994; McKinnon & Docherty, 2001). The biallelic mutation of PDX1 leads to agenesis of the pancreas both in mice (Jonsson et al, 1994) and in pigs (Kang et al, 2017; Wu, Vilarino et al, 2017), and results in infant death, whereas in mice, monoallelic disruption impairs insulin secretion from pancreatic β‐cells (Brissova et al, 2002). To our knowledge, however, viable PDX1 monoallelic mutants have not been investigated in pigs because PDX1 disrupted pigs were generated by somatic cell nuclear transfer (SCNT) with PDX1 biallelic mutant cells in the previous study (Kang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In brief, precise genome editing technologies are widely used in cattle and other domestic animals to improve transgenesis (Menchaca et al, 2016;Niu et al, 2017;Wu et al, 2017), and most of these studies rely on TN technology to produce live offspring. It is possible that the knowledge gained through the CRISPR-Cas 9 system may soon be used in cloning production.…”
Section: Perspectives In Animal Transgenesis and Conclusionmentioning
confidence: 99%